Giant Solitary Trichoepithelioma: A Case Report - KC, Geetika; KC, S.R.; Lakhey, A.; Singh, M. (Nepal Medical College Journal, 2019)
Giant solitary trichoepithelioma (GST) is a rare adnexal skin tumor with hair structure differentiation. It varies from trichoepithelioma in size (>2cm) and location (common in thigh and perianal region). So far only 18 cases of GST have been reported worldwide. This is a case of GST in the thigh of a 42 year old man. This form of trichoepithelioma can be a cellular tumor which needs to be differentiated from trichoblastoma, keratotic basal cell carcinoma, nevoid basal cell carcinoma and microcystic adnexal carcinoma.